A estratégia da intersetorialidade como mecanismo de articulação nas ações de saúde e assistência social no município da Cajazeiras-PB - Batista, Káttia Gerlânia Soares (2015)
With the promulgation of the Constitution of 1988 and the advent of the magnifying of the social rights and consequently the change in the management of the politics of social cut in Brazil, the question of the intersectoral starts to be each more present time in the academic debate. In this direction, some social politics currently bring in its agendas the proposal of the intersectoral. Among them, the politics of Health and Social Assistance are distinguished, which, when pointing with respect to the proposal intersetorial, leave evident the necessity to materialize the integral protection that informs the Brazilian system of Social security. From these reflections, this study it searched to analyze the strategy of the intersectoral as mechanism of joint in the criminal actions of Health and Social Assistance in the City of Cajazeiras-PB. In this direction, we analyze the conceptions concerning the intersectoral from the speech of the professionals who act in the ESF and CRAS I and II of the related city. The sample was intentional and the criterion of eligibility for delimitation of the group of professionals, was the fact to be has at least one year in the assistance or health service. In this manner, 14 professionals had been interviewed, being 08 (eight) professional ones that they act in the teams of ESF I and II, and 06 (six) professional that they act in CRAS I and II. Amongst the professionals, we detach: 02 Social Doctors, 02 Nurses, 02 Dentists, and 02 Coordinators, who act respectively in the teams of ESF I and II, and two Assistants, two Psychologists and two Coordinators, who act in CRAS I and II. We also objectify, to identify the challenges of the intersectoral in the field of the politics of Health and Social Assistance, looking for to evidence of that way the professionals come contributing with the effective of the intersectoral in the daily one of its action. The methodology for the accomplishment of this study if based on a descriptive exploratory research with qualitative boarding. For in such a way, we use the interview technique, with application of an instrument previously elaborated I contend subjective and objective questions, after the assent legalized verbally and in writing. The collected data had been processed of the point of view qualitative and analyzed through the content analysis, leaving of the thematic analysis. Although the texts of the public politics are consensuals on the relevance of the intersectoral, the interviewed professionals demonstrate that its concretion still is challenging, a time that coming up in a contradictory environment marked by the impediments in the management of the politics and the services. In this perspective, we consider that the intersectoral finds limits in such a way to be materialized in the work developed for the team of the ESF how much in the CRAS, therefore the boarding of the social problems occurs in fragmented way and the attempts of intersectoral joint between the public politics are scarce, prompt and compensatory.